(untitled) (Bangladesh Journal of Medical Education, 2012)
This cross-sectional study was conducted with the objective to explore the practice of clinical teaching in Dermatology of undergraduate medical students of Bangladesh to identify the constraints and suggestions to improve the clinical teaching. The study also looked into the clinical competencies achieved by the students from available facilities provided by the institutes. The study was conducted at Dhaka Medical College (DMC) and Sir Salimullah Medical College (SSMC) from July 2008 to June 2009. The students of 4th year and 5th year were the study population. Sample size was 273. After taking permission from concern authority data were collected through a self administered semi-structured questionnaire by convenient sampling. The study reflected that most of the clinical classes in Dermatology were taken by the junior teachers and mid level teachers. It was found that majority of clinical classes were held in the morning and afternoon, though a very few of the clinical classes are taken at night in Dermatology. The students viewed that the teachers follow the curriculum to conduct the clinical classes. The students agreed that they were benefited through those clinical classes and acquired how to examine the patients and to take history and other clinical skills. Majority of the respondents viewed that inadequate number of teachers and patients were one of the important barriers for clinical teaching in Dermatology. They suggested that the senior teachers should conduct clinical teaching with sufficient instructional materials and instruments. It was recorded that the clinical teaching in Dermatology should be integrated in the institutes. It was also proposed that sufficient number of relevant patients and adequate number of teachers should be ensured for imparting effective clinical teaching in Dermatology. DOI: http://dx.doi.org/10.3329/bjme.v1i1.12854 Bangladesh Journal of Medical Education Vol.1(1) 2010 pp.16-24